Meningkatkan Aktivitas Belajar Peserta Didik Melalui Metode Bermain Peran Pada Mata Pelajaran Pkn Kelas V Sd Muhammadiyah 2 Limboto Kabupaten Gorontalo - Fratiwi Tina (Syntax Idea)
Low student learning activity is one of the challenges in education, particularly in Civics Education (PKn). This study aims to analyze the effectiveness of the role-playing method in improving student learning activity in Grade V at SD Muhammadiyah 2 Limboto, Gorontalo Regency. This research employs a classroom action research (CAR) method with a cyclical design, consisting of two cycles, each comprising three meetings. The study subjects were 20 students, including 9 boys and 11 girls. The results indicate that before the intervention, only 30% of students were actively engaged in learning. After implementing the role-playing method, student learning activity gradually increased. In Cycle I, learning activity improved from 45% in the first meeting, 55% in the second meeting, and 65% in the third meeting. The increase continued in Cycle II, reaching 70% in the first meeting, 75% in the second meeting, and 90% in the third meeting. The findings suggest that the role-playing method can be an effective instructional strategy to enhance student engagement and learning activity. Therefore, teachers are encouraged to integrate this method into the teaching process to create a more interactive and enjoyable learning environment.